Evaluación del perfil bioquímico renal en cobayos sometidos a tres dietas alimenticias. - Logacho Guamán, Mireya Mishell (2025)
The guinea pig, scientifically known as Cavia porcellus, stands out for its considerable potential to become a profitable economic activity within the livestock industry. Therefore, in the present research work we sought to evaluate the renal biochemical profile in guinea pigs subjected to three different diets. The study was carried out with 48 guinea pigs of 21 days of age, distributed equally by sex and organized in four treatments: T0 (100% forage), T1 (70% forage, 30% balanced), T2 (50% forage, 50% balanced) and T3 (40% forage, 60% balanced), with two replicates of six animals per treatment. A Randomized Complete Block Design (RCBD) was used, supplemented with an analysis of variance (ADEVA) and Tukey's test at 5% to determine significant differences between treatments. The results of the study revealed that the higher R2T3 (40% forage, 60% balanced) diets significantly impacted the renal biochemical profile of the guinea pigs, showing elevated urea and creatinine levels at baseline and persistent urinary crystal formation in all treatments at the end of the study. Treatments with a lower proportion of feed (R2T1 70% forage, 30% balanced and R2T2 50% forage, 50% balanced) showed better creatinine normalization, but without completely eliminating crystal formation. The exclusively forage-based treatment (R2T0 100% forage) showed lower growth efficiency and altered metabolic parameters, highlighting the importance of a proper balance between feed and forage in the diet to optimize both growth and renal health. These findings emphasize the need to monitor diet composition to prevent renal impairment in guinea pigs